2(7x+9)=8x+6

Simple and best practice solution for 2(7x+9)=8x+6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(7x+9)=8x+6 equation:


Simplifying
2(7x + 9) = 8x + 6

Reorder the terms:
2(9 + 7x) = 8x + 6
(9 * 2 + 7x * 2) = 8x + 6
(18 + 14x) = 8x + 6

Reorder the terms:
18 + 14x = 6 + 8x

Solving
18 + 14x = 6 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
18 + 14x + -8x = 6 + 8x + -8x

Combine like terms: 14x + -8x = 6x
18 + 6x = 6 + 8x + -8x

Combine like terms: 8x + -8x = 0
18 + 6x = 6 + 0
18 + 6x = 6

Add '-18' to each side of the equation.
18 + -18 + 6x = 6 + -18

Combine like terms: 18 + -18 = 0
0 + 6x = 6 + -18
6x = 6 + -18

Combine like terms: 6 + -18 = -12
6x = -12

Divide each side by '6'.
x = -2

Simplifying
x = -2

See similar equations:

| 2.2q-1.9-5.9q=4.7q-3.1 | | r^2=-56-15r | | 3y-9+y+47=6y+40-4y | | -13-x=x-5 | | -4(3p+2)-46=3(4p+6) | | -2x-9=6x+15 | | 3.1(6.7+4.7n)=38.304+6.6n | | p^2+8p=0 | | 5(c-3)+9=3+c-9 | | 20+4x=8(x+6) | | 8x+3=6x+7 | | 3-6x=-(1-3x)+4 | | 8(x+4)+6=38 | | -24+3k=k-2k | | (4x^2)+16x+13=0 | | 13.7v-6.5=-2.3+8.3 | | n^2=-5n | | 2(x+4)-5x+7= | | 0=-6(y+2) | | 5=4(x-2)+9 | | 7+6x=-4(x-5)+7 | | 12-1.2(x-5)=22-2(x-4) | | -4(t+6)=4 | | -3-8x+5x=4-4x | | n^2+6n=-5 | | 3k+8k=8k-9 | | 5(x-7)+2=-28 | | 3x+5=3(x-9) | | -5(z+7)=-6z | | x*2-x=12 | | 5n-4(n-6)=2+2n | | 10-(3y-3)=2-4y |

Equations solver categories